Assessment of groundwater vulnerability to pollution by modified DRASTIC model and analytic hierarchy process - Jhariya D.C.; Kumar T.; Pandey H.K.; Kumar S.; Kumar D.; Gautam A.K.; Baghel V.S.; Kishore N. (My University, 2025)
Effective management of the groundwater resources became an important factor for the growth of urbanized areas, especially for the sector which has considerable agricultural and industrial activities. Along with quantity, assessment of the groundwater quality also plays an important role in its growth. Tandula watershed is one of the populated areas in the Balod district, Chhattisgarh state, which needs an assessment on the groundwater vulnerable zones for its effective management. The vulnerable zones of the study area have been assessed with the help of DRASTIC, DRASTIC–AHP, and modified DRASTIC–AHP methods. The models have been developed with the help of seven parameters which are depth to water, net recharge, aquifer media, soil media, topography, the impact of vadose zone, and hydraulic conductivity. The resulted groundwater pollution vulnerability in the study area has classified into five categories such as very low, low, moderate, high, and very high. Cross-comparison and validation of the model with 77 groundwater samples which contain Nitrate concentration were considered and concluded that the modified DRASTIC–AHP model is most accurate and suitable for the present study area. The study also revealed that groundwater in the study area is contaminated by Nitrate pollution due to excessive application of fertilizers in agricultural activities and improper sewage disposal. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.